Contrastive Analysis Of Various Speech Events In English and Batak Toba - Destri Yani Puspita Sari Gultom; Yohana Anggita Sidabutar; Theresa Nanda Kristina; Anita Sitanggang (CV Putra Publisher, 2023)
This research to compares and contrasts by analyzing various speech events in English language and Batak toba language. To show that in English and Batak toba language there are formal and informal language differences in life. This study aims to compare how the expressions are found in English and Batak toba language. Qualitative method was used in this research. Comparing the nine expressions in English and Batak toba language, they have similarities in expression, namely in